Fabrication of graphene oxide/titanium dioxide hybrid material for solar cell and membrane application - Muqoyyanah (2019)
This study aimed to fabricate graphene oxide (GO)/titanium dioxide (TiO2) hybridbasedmaterial for dye-sensitized solar cells (DSSCs) and membrane separationapplications. The electrochemical exfoliation assisted by customized triple-tail sodium1, 4-bis (neopentyloxy)-3-(neopentyloxycarbonyl)-1, 4-dioxobutane-2-sulphonate(TC14) and commercially available single-tail sodium dodecyl sulphate (SDS)surfactants were used to synthesize GO with water-based electrolyte and N, Ndimethylacetamide(DMAc) as solvents. The chemical reduction process utilizinghydrazine hydrate was then performed to produce reduced GO (rGO) which furtherhybridized with multi-walled carbon nanotubes (MWCNTs). The fabrication of DSSCscounter electrode (CE) was done by spraying deposition method on fluorine-doped tinoxide (FTO) as substrate and also coated by thin platinum (Pt). Meanwhile, differentvariety of TiO2 nanostructures as DSSCs photoanode were synthesized byhydrothermal growth and squeegee methods with different recepi and synthesis time.On the other hand, the DMAc-based GO was used to fabricate nanofiltration (NF)membrane utilizing polyvinylidene fluoride (PVDF) as the main polymer material byusing phase inversion method. The DSSCs and NF membrane samples werecharacterized using solar simulator and dye rejection test, respectively. The DSSCsfinding showed that the highest energy conversion efficiency (1.559%) was achievedby TiO2 NRs-NFs/TC14-rGO/TiO2 NPs as photoanode and TC14-rGO_MWCNTs/Ptas CE with the value of open circuit voltage, short circuit density, and fill factor were0.747 V, 3.275 mA/cm2, and 53.5, respectively. Meanwhile, the NF membrane findingshowed that PVDF/SDS-GO/TiO2 presents the highest dye flux (10.148 L/m2h) andhigh dye rejection efficiency (~92.76%). In conclusion, the synthesized GO showed apotential to be applied as electrode thin films and also membrane materials. Implicationof this study is a novel, simpler, low-cost, and less harsh chemical for the GO synthesisto fabricate CE and photoanode film for DSSCs and also NF membrane.